A report on the practice in industry in fish preservation. - Martinez, Myrna B. (Miagao, Iloilo College of Fisheries, University of the Philippines, 1964)
The four months practice in industry is a practical training in all of the important fishing industries theoretically and practically learned by fishery technologist for two solid years. This is to mold each of them to skilled technologists, to produce best products for the benefit of one's country. Thru their continuous practice may raise successful and profitable industries, which would contribute to the economy of Filipino people. Furthermore, numerous information was inculcated in their minds, to remain in them, as stepping-stones on their way to success.
Keywords: Fish-Preservation.